Concepción De Formación Y Actividad Física En Población Habitante De Calle Consumidora De Bazuco De La Ciudad De Armenia, Quindío (2016)
The controversy derived from the use of psychoactive substances, is currently one of the causes that make society a conglomerate of events that threaten against the personal and social development; therefore, knowing the conceptions of education and physical activity that the population who inhabit the streets and drug, (bazuco) consumers of Armenia city, (Quindio), which allowed in a systematic way giving response to that event which promotes the reseaercher´s interest, sincé using using research Methods such as micro etnography, which from its form of intervention allows an immersion in the raised context and the natural interaction with the research subjects; in this regard, there were used tools whose procedure ways, facilitated the comprenhension of the conceptions and in this regard they allowed to go beyond of what society percibes, giving the possibility from the contexts to manifest according to their lifestyle, what each individual conceived before the research question ¿Which is the conception of education and physical activity into the homeless population and bazuko consumer of Armenia (Quindio) city? Key